Vulnerability and welfare: Findings from the fifth round of the Myanmar Household Welfare Survey (March – June 2023) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The fifth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between March and June 2023. It follows from four rounds that were carried out quarterly beginning in December 2021. This report discusses the findings from the fifth round related to livelihoods, shocks, asset and income poverty, and coping strategies.